Creativity of Gandes Luwes Traditional Arts Studio From Parenggan Village, Pati in Developing Tembang Dolanan Performance - Nirbaya, Eryaya; Hartono, Hartono; Utomo, Udi (Universitas Negeri Semarang, 2017)
Gandes Luwes traditional dance studio plays important roles in conserving traditional arts, especially tembang dolanan (traditional game song) as the musical art made based on the growth level of children. Beside used as a song, Tembang Dolanan also contains moral values or wisdoms as well as be enhanced with the creativity from the creator studio in its structure and rhythm pattern. This research reviewed or analyzed the forms and creativity of Tembang Dolanan. This research used qualitative approach by understanding and describing the phenomenon of creative backsound music as to fulfill the needs of the market or the society to support the development of Tembang Dolanan.